Inventory of Superior Durian from the Highlands and Lowlands in Fakfak Regency - Inna Martha Rumainum; Yohanis Amos Mustamu; Ishak Musaad; Umi Yuminarti; Chairat Burana (Jurnal Ilmu Pertanian Indonesia, 2025)
The purpose of this study is to catalog exceptional durians from both the highlands and the lowlands of Fakfak Regency in West Papua Province. The inventory included both highland and lowland durian accessions. In the highlands, there were 8 durian accessions, whereas in the plains there were seventeen. Fruit size, fruit skin thickness, fruit pulp color, fruit pulp thickness, aroma, sweetness level, fruit pulp fiber, seed size, and seed count were utilized as evaluation criteria. Each criterion tested showed variability. This demonstrates that genotypic variability exists among durian accessions from the Fakfak Regency. According to the characterization results, there were six lowland accessions that could be classified as superior in terms of fruit size, thickness of fruit pulp, level of sweetness, pulp fiber, and aroma: Pahger Nkendik, Katemba, Danaweria2, Brongkendik, Air Besar, Kanantare, and Sakartemin. Keywords: durian, Fakfak, superior fruit